Adaptive Governance Features from Stakeholder Issues in Lake Limboto Management - Akbar, Muh. Firyal; Alwi, Alwi; Indar, Nur Indrayati Nur; Abdullah, Muhammad Tang (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
This study aims to examine adaptive governance aspects of the issues from each stakeholder related to the management of Limboto Lake. The implementation of this research uses a qualitative deductive approach. The types of research that will be used are descriptive and explanative types. Sources of data from this research, namely documents and archival records grouped into documentation sources, interviews sourced from people/informants, and direct observation, observation of the role of physical devices grouped in observation sources, and Focus Group Discussions (FGD). The results of this study indicate that efforts to revitalize, rehabilitate and conserve are, of course, not the task of the Government alone but require the participation of the community in them. Conditions of good synergy between the Government, the community and the private sector in efforts to save and manage Lake Limboto are desirable, this is also in line with the achievement of the objectives of adaptive governance in terms of resilience to rapid and unpredictable environmental changes.